Sedimentation in Dune Forests, Mangrove Forests and CC Block System and Associated Topographic Changes (Journal of Bangladesh Academy of Sciences, 2019)
This paper is concerned with the deposition of sediment due to dune forests (Nakatajima dune, Japan) and CC block system on a riverbank (Padma, Bangladesh). Measurements of sediment deposition were carried out at Nakatajima dune, Japan and at Padma riverbank, Rajshahi, Bangladesh using Global Positioning System (GPS). 2442 m3 sediment migrates each year to the East side of Nakatajima dune by wind and the edge of the dune develops about 6-7 m/year due to the existence of forests. Sedimentation rate is also greater in shallower mangrove areas. The trapped sediment height varies from 8.0 to 10.0 cm in the mangrove-lined bank. Mangrove forests help to trap 25% more sedimentation at low tide than at high tide. On the other hand, only for setting up the CC block and groynes along the bank, the sedimentation rate is observed almost twice than that of the previous year. An analysis shows that there is a similarity of sedimentation among dune, beach forests, mangrove forests and CC blocks.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 1, 67-78, 2019